Green Strategies for the Preparation of Enantiomeric 5–8-Membered Carbocyclic β-Amino Acid Derivatives through CALB-Catalyzed Hydrolysis - Sayeh Shahmohammadi; Tünde Faragó; Márta Palkó; Enikő Forró (Molecules, 2022)
Candida antarctica lipase B-catalyzed hydrolysis of carbocyclic 5–8-membered cis β-amino esters was carried out in green organic media, under solvent-free and ball-milling conditions. In accordance with the high enantioselectivity factor (E > 200) observed in organic media, the preparative-scale resolutions of β-amino esters were performed in tBuOMe at 65 °C. The unreacted β-amino ester enantiomers (1R,2S) and product β-amino acid enantiomers (1S,2R) were obtained with modest to excellent enantiomeric excess (ee) values (ees > 62% and eep > 96%) and in good chemical yields (>25%) in one or two steps. The enantiomers were easily separated by organic solvent/H2O extraction.